The spiritual background of early Islam : studies in ancient Arab concepts - Bravmann, M. M. (Brill Classics in Islam, 2009)
In a series of essays devoted to key terms and ideas in Islam, Bravmann argues on the basis of pre-Islamic and early Islamic texts for an Arabian background to the rise of the religion. In pursuing a through philological examination of the evidence, Bravmann finds core values and ideas of Islam deeply embedded in ancient Arab linguistic expression. His work continues to provide a critical element in the debates about the emergence of Islam and cannot be ignored by anyone trying to assess the complex historiographical problems that surround the issue.